Ruthenium Complex "Light Switches" that are Selective for Different G‐Quadruplex Structures. Issue 2 (12th November 2015) - Wachter, Erin; Moyá, Diego; Parkin, Sean; Glazer, Edith C.
Abstract: Recognition and regulation of G‐quadruplex nucleic acid structures is an important goal for the development of chemical tools and medicinal agents. The addition of a bromo‐substituent to the dipyridylphenazine (dppz) ligands in the photophysical "light switch", [Ru(bpy)2 dppz] 2+, and the photochemical "light switch", [Ru(bpy)2 dmdppz] 2+, creates compounds with increased selectivity for an intermolecular parallel G‐quadruplex and the mixed‐hybrid G‐quadruplex, respectively. When [Ru(bpy)2 dppz‐Br] 2+ and [Ru(bpy)2 dmdppz‐Br] 2+ are incubated with the G‐quadruplexes, they have a stabilizing effect on the DNA structures. Activation of [Ru(bpy)2 dmdppz‐Br] 2+ with light results in covalent adduct formation with the DNA. These complexes demonstrate that subtle chemical modifications of Ru II complexes can alter G‐quadruplex selectivity, and could be useful for the rational design of in vivo G‐quadruplex probes. Abstract : G‐quadruplex light switches : The addition of a bromine substituent to the dipyridylphenazine (dppz) ligands in the photophysical "light switch", [Ru(bpy)2 dppz] 2+, and the photochemical "light switch", [Ru(bpy)2 dmdppz] 2+ (see graphic), creates increased selectivity for G‐quadruplexes and provides a scaffold for rational design for in vivo probes.